Vote Dilution and Suppression in Indian Country. Issue 1 (9th April 2015) - Schroedel, Jean; Hart, Ryan
<x content-type="archive" xml:space="preserve">Abstract</x> The struggle for Native American voting rights has lasted more than two centuries. Although the 1924 Indian Citizenship Act granted citizenship to indigenous peoples born within the geographic boundaries of the United States, it did not ensure the right to vote. Because the Constitution gives states the power to determine the "times, places, and manner of holding elections, " many states statutorily denied Native Americans the franchise until federal lawsuits forced them to change. Having the statutory right to vote, however, did not ensure that it could be exercised in a meaningful way. Since the passage of the 1965 Voting Rights Act there have been more than ninety voting rights cases involving Native Americans. While the overall historical trend has been toward extending the vote, periods of enhanced voting rights often have been followed by periods of retrenchment. In this article, we argue that the traditional frameworks used to explain racial inequalities fail to account for the unique character of relations between indigenous peoples and the U.S. government, and we propose a tripartite approach that draws from studies in core–periphery development and "racial institutional orders, " but also considers the many ways that tribal identities intersect with these.